Ferramentas para análise filogenética e de distribuição taxonômica de genes ortólogos - Tetsu Sakamoto (2016)
Studying the evolutionary relationships between organisms is a subject that has fascinated scientists for a long time and the approaches to analyze and infer the evolutionary history has been modified as new technologies and new data types emerge. At first, the morphological and embryogenic data were the main source for phylogenetic analysis, but molecular data, such as nucleotide or amino acid sequences, have ruled the field of phylogenetic studies since the introduction of automated DNA sequencer in the mid 80s. Although molecular phylogenetic had received significant methodological improvements during this time, there are still several unresolved parts in the tree of life. Development and popularization of large-scale sequencing technologies came to help inelucidating the gaps in the evolutionary history, but they also impose newmethodological challenges, since several common procedures in molecular phylogeny do not deal with a large amount of sequences generated by these machines. In this context, the objectives of the present work were to develop molecular phylogenetic tools that meet the current demands in molecular phylogeny. We developed three applications in this work: (1) TaxOnTree, (2) HyperTriplets and (3) ELDOgraph. TaxOnTree is a tool that includes taxonomic data into a phylogenetic tree. The trees generated by this tool provide users with an easy and fast way to access all taxonomic information of the samples in the tree, as well as the evolutionary relationship between them based on the taxonomic tree from NCBI Taxonomy. The HyperTriplets is a tool that reads and processes several gene trees to reconstruct a supertree based on analysis of triplets. Approaches that fill some gaps in the supertree methodology, as the restriction on using gene trees with paralogs and the lack of distance values in the supertree branches, were developed and implemented in this tool. Finally, the ELDOgraph is a tool that extracts the phylogenetic distances in several gene trees to perform a comparative analysis amongst the sampled species. This tool provides a new approach to verify and visualize the evolutionary proximity in adistinct way from the tree structure approach. All three tools are available at http://biodados.icb.ufmg.br/taxonphylotools.